Impossible Trinity in a Small Open Economy: A State–Space Model Simulation - Bhatta, Guna Raj; Nepal, Rabindra; Jayanthakumaran, Kankesu; Harvie, Charles (Asian Development Policy Review, 2022)
Should monetary policy independence be maintained when the exchange rate is fixed under closed capital account conditions in a small open economy? In this study, we simulate the impossible trinity condition during 1989 to 2019 on the Nepalese economy that restricts capital flows and fixes the exchange rate with India. We modify the traditional Taylor rule based on the monetary policy reaction function to characterize Nepal’s economic conditions more closely. The state–space model simulation shows that the policy trilemma does not hold in Nepal, such that the model can predict interest rate when the weight for domestic conditions is assigned at a substantially lower level. Therefore, the existing policy mix may need to be revisited to maintain monetary policy independence. Nepal might consider devaluing its currency to neutralize the adverse effects of the negative risk premium and ameliorate the real exchange rate appreciation in the short run and explore alternative arrangements in the long run.